Analysis and improvement of a tea value chain - Korrakot Y. Tippayawong (2018)
The aim of this paper is to improve performance of a tea company using value chain analysis. The company value chain activities were investigated. Analysis of current production practice was analyzed using a failure mode & effect analysis (FMEA) technique to perform a risk assessment within the manufacturing process weaknesses. Linear programming method, based on fast moving product theory and the Lingo program was used as a tool to calculate a suitable model. Activity in warehouse storage was selected to improve and accommodate future product expansion and ordering. With the new warehouse layout, the use of space can be improved by more than 38% for storage products and the distance to transport can be reduced by almost 23%. The result can be used as a guideline for other companies in the tea industry to improve their process activities.